Rejuvenating Public-Private Partnerships (PPPs) in Asia - Bhatia, Dr. (Mrs) Satinder (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
Infrastructure-building has become a focus area in Asia as targeted GDP growth rates climb higher.Â Selection of projects as PPP projects or pure public sector projects has to be done carefully comparing costs and benefits under both scenarios.Â Such an approach (value for money) is common in the UK and Australia which have considerable experience in PPP projects.